Male prostitution - integrative review - Cerdeira de Souza, Daniel (2023)
The aim of the study was to analyze the literature on male prostitution. This is an integrative literature review that had as its universe 25 articles available in the Virtual Health Library and Portal Periódicos Capes. Data were analyzed via content analysis procedure. The results were organized into six categories: 1) Male sex workers; 2) Health-related demands; 3) Risks and violence related to sex work; 4) Secrecy and theatricality of male sex work; 5) Gender, masculinity and value of the anus; 6) Territories of male prostitution. It was possible to perceive men are the biggest consumers of male sexual services, and that nuances related to the performativity of masculinity and secrecy are essential for the implementation of the programs. It is concluded that male prostitution involves power relations based on a multitude of factors related to gender, race and class that need public policy attention.